OPTIMASI PARAMETER EDM SINKING PADA MATERIAL BAJA SKS3 MENGGUNAKAN METODE RESPONSE SURFACE - Isanda Ika Damayanti; Bayu Wiro Karuniawan; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The material of the workpiece is one of the non-electrical parameters that affect the performance of EDM Sinking. SKS-3 steel is a steel with a high carbon class and in its application this material is commonly used for products for making bending die, sizing and stamping tools for medium run, and cutting blades. In this study using the response surface method with 15 run orders and 3 replications by applying Box-Behnken Design for research experiment design and ANOVA to analyze data. Based on the results of the analysis, it was found that the optimal combination of parameters was Pulse current 7.29293 A, Pulse on time 5.34343 (?s), and Pulse off time 3 (?s). To produce optimal dies products, the factors studied are the influence of process variables such as pulse current, on time, and off time on the material removal rate and surface roughness in the machining process using EDM Sinking and to determine the right combination variable settings of process parameters such as pulse current, on time, and off time in order to produce products with optimal material removal rate and surface roughness in the process EDM Sinking